Entrepreneurial Behaviour of Tribal Women regarding Vermiculture Technology - Vyas, Latika; Jani, Piyush (Journal of Agricultural Extension Management, 2018)
The study was conducted in purposively selected Rechhawar village of ihadol block of Udaipur district in order to know the entrepreneurial behavior of tribal women in terms of their socio-economic, psychological and family background attributes. The results of the study revealed that majority of the respondents exhibited medium to low level of entrepreneurial behavior while very few of them exhibited high level of entrepreneurial behavior The study further shows that education, family income, risk willingness of the respondents and training received by them had positive relationship with their entrepreneurial behavior The study also concluded that age, family occupation, owning responsibility for failure, family type, family size, birth status in parental home, present status in in-law’s home and length of experience had negative relationship with entrepreneurial behavior It is further concluded that dual responsibility, lack of responses, poor family support, late payment by clients, mobility and marketing constraints were the major impediments perceived by the tribal women.